IMPLEMENTASI KEARIFAN LOKAL “SEDINTEN BERBUDAYA JAWI” DI SD NEGERI TEMAS 01 BATU - Izza Audia Rohmawati; Rosichin Mansur; Muhammad Sulistiono (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
This research is based on the implementation of local wisdom in sedinten berbudaya Jawi at SDN Temas 01 Batu. The purpose of this study is to describe the forms, the implementation of local wisdom, and the supporting factors and factors inhibiting the implementation of local wisdom in sedinten berbudaya Jawi in SDN Temas 01 Batu. The purpose of this study is to describe the planning, implementation approach to the type of case studies. Data collection procuderes uses documentation, interviews, observations. Data analysis uses data reduction, data presentation, and drawing conclusions. The results of this study are by implementing local wisdom in sedinten berbudaya Jawi so that it can improve students' understanding of jawi culture which is currently displaced by globalization.